Fatty Acids from Different Fat Sources and Dietary Calcium Concentration Differentially Affect Fecal Soap Formation in Growing Pigs. Issue 5 (20th April 2021) - Stroebinger, Natascha; Rutherfurd, Shane M; Henare, Sharon J; Hernandez, Jose F Perez; Moughan, Paul J
ABSTRACT: Background: Calcium (Ca) can complex with free fatty acids in the gastrointestinal tract (GIT), leading to the formation of insoluble unabsorbable Ca-fatty acid soaps, contributing to the proposed effect of Ca on weight loss in humans. Objectives: We determined the effect of dietary Ca concentration and the individual long-chain fatty acids on Ca-fatty acid soap formation and fatty acid digestibility. Methods: Nine-week-old crossbreed male pigs ( n  = 144; mean ± SD body weight: 21.7 ± 0.15 kg) were used as an animal model for digestion in the adult human. The animals received purified diets containing 4 Ca concentrations (0, 2, 4, and 6 g/kg diet) and 4 fat sources (tallow, palmolein oil, soybean oil, and olive oil) in a completely randomized design. Fatty acids, Ca, and Ca-fatty acid soaps were determined in feces ( n  = 9 per diet). Results: Increasing dietary Ca led to a 4-fold increase ( P  ≤ 0.05) in excreted palmitic and stearic acid when diets contained tallow or palmolein oil as the major fat source. More than 80% of these excreted fatty acids were present as soaps. For the tallow-based diets, increasing dietary Ca led to a decrease in stearic acid digestibility from 91% to 66% ( P  ≤ 0.01) and in palmitic acid digestibility from 96% to 83% ( P  ≤ 0.01). For the olive oil- and soybean oil-based diets dietary Ca did not ( P  > 0.05) influence fatty acid excretion. Conclusions: Ca-fatty acid soap formation led to decreased fat absorption in the GIT of growing pigs, which supports the hypothesis that higher dietary Ca concentrations reduce fat absorption.